Tannic acid delayed dietary fiber fermentation: dual mechanisms of enzyme inhibition and microbial community dynamics - Ren, Liping; Wang, Haoqiang; Luo, Shunjing; Liu, Chengmei; Hu, Xiuting (Frontiers in Microbiology, 2026)
This study examined the influence of tannic acid (TA) on the fermentation rate of inulin (INU), fructooligosaccharides (FOS), galacto-oligosaccharides, xylo-oligosaccharides, isomalto-oligosaccharides, and β-glucan. It was found that 1.5 μmol/mL TA decreased production of gas and short-chain fatty acids from fermentation of these fibers, confirming that TA decreased the fermentation rate. Moreover, 1.5 μmol/mL TA inhibited the activity of β-fructosidase, xylanase, β-galactosidase, α-glucosidase, and β-glucanase secreted by gut bacteria and decreased the fermentation rate of glucose, fructose, xylose, and galactose. In summary, TA inhibited the activity of enzymes that participated in metabolism of dietary fibers and thus decreased the fermentation rate. On the other hand, INU and FOS were selected as representatives of dietary fibers, and the effect of interplay between TA and INU or FOS on the composition of gut microbiota was analyzed. TA and FOS or INU selectively promoted the growth of different specific genera, which might also result in the decrease in the fermentation rate. Moreover, co-fermentation of TA and FOS or INU increased the abundance of beneficial bacteria, including Faecalibacterium and Coprococcus, at the late fermentation stage, which suggest that decreasing the fermentation rate of fibers was beneficial for the distal colon health.